2007
DOI: 10.1002/jcp.21058
|View full text |Cite
|
Sign up to set email alerts
|

The immunomodulatory protein SV‐IV protects serum‐deprived cells against apoptosis but not against G0/G1 arrest: Possible implications for the survival of implanting embryo

Abstract: Serum deprivation induced in human lymphoblastoid Raji cells oxidative stress-associated apoptotic death and G0/G1 cell cycle arrest. Addition into culture medium of the immunomodulatory protein Seminal vesicle protein 4 (SV-IV) protected these cells against apoptosis but not against cycle arrest. The antiapoptotic activity was related to: (1) decrease of endocellular reactive Oxygen species (ROS) (2) increase of mRNAs encoding anti-oxidant enzymes (catalase, G6PD) and antiapoptotic proteins (survivin, cox-1, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 76 publications
4
15
0
Order By: Relevance
“…2).These data are consistent with similar binding observations already published (Metafora et al, 1989;Morelli et al, 2007). (Stiuso et al, 1999;Romano-Carratelli et al, 2002).…”
Section: Sv-iv Fitc and [ 125 I]sv-iv Binding To The Surface Of Humansupporting
confidence: 92%
See 4 more Smart Citations
“…2).These data are consistent with similar binding observations already published (Metafora et al, 1989;Morelli et al, 2007). (Stiuso et al, 1999;Romano-Carratelli et al, 2002).…”
Section: Sv-iv Fitc and [ 125 I]sv-iv Binding To The Surface Of Humansupporting
confidence: 92%
“…Similar results were obtained with resting or antigen-stimulated CTLs. In addition, the possibility that the immunosuppression was due to aspecific cytotoxic properties can be ruled out by the following observations: 1) immunosuppression was detectable on activated MNC (see Results) only at low concentrations (5 to 30 M), rich in biologically active SV-IV monomers; at similar low concentrations SV-IV did not inhibit but, in contrast, stimulated quiescent lymphocytes to synthesize and release specific cytokines (Tufano et al, 1996); 2) at concentrations higher than 30 M, rich in biologically inactive SV-IV trimers, no cytotoxic effects were observed (Stiuso et al, 1999); 3) the inhibitory effects of SV-IV on proliferation were found only for immunocompetent cells (Metafora et al, 1989); 4) in addition, SV-IV has been recently demonstrated to possess intrinsic antiapoptotic activity (Morelli et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations